Cultural models of gender identity in women - Колпак, Тетяна Володимирівна (Psychological Counseling and Psychotherapy, 1970)
The work is devoted to the study of psycho-semantic features of cultural models of female gender identity in girls students. Dedicated 5 psychosemantic models that relate to cultural models of female gender identity: "Business", "Female professional", "Bright" - " intellectual Female", "Feminine" - "Keeper", "Strong" - "Strong woman", "Model" "Barbie". Analyzed the features to identify girls with the most prevalent cultural models of female gender identity.